Sebuah Laporan Kasus: Cholelithiasis dengan Cholesystitis Akut pada Tn. Y 27 Tahun - Dewi, Yofira Sintya; Yusmaidi, Yusmaidi (CV. Jasa Sukses Abadi, 2024)
Gallbladder disease is associated with a malfunctioning gallbladder and highly concentrated bile, leading to conditions such as the formation of gallstones or cholelithiasis. Cholelithiasis can occur due to high concentrations of cholesterol in the gallbladder. Obstruction of the cystic duct, either by stones or functional issues, can cause acute inflammation of the gallbladder. Acute cholecystitis attacks are often associated with gallstones, or cholelithiasis. Common symptoms include right upper quadrant or epigastric abdominal pain, especially after consuming fatty foods, with additional symptoms such as nausea, vomiting, fever, and diarrhea. The development of this disease is believed to involve many factors and likely arises from complex interactions between various genetic and environmental elements. An imbalance in bile composition, characterized by excessive cholesterol secretion, reduced gallbladder motility, and the accumulation of mucin gel, contributes to the formation of gallstones. Gallbladder disease related to cholesterol results from a biochemical imbalance involving lipids and bile salts in the bile stored in the gallbladder. A 27-year-old patient, Mr. Y, has several risk factors that increase the development of the disease, and the following case report discusses the clinical presentation and laboratory examination results related to the onset of this disease. Laparoscopic cholecystectomy was performed on the patient, and appropriate education was provided, illustrating the importance of intra-professional collaboration and positive outcomes for the patient.